Climate change impacts on species planting domains: a preliminary assessment for selected plantation forests in Fiji, Papua New Guinea and the Solomon Islands. (1st April 2014) - Booth, T.H.; Jovanovic, T.
A simple method is applied to provide a preliminary assessment of climate change impacts on the species planting domains for Tectona grandis (teak), Swietenia macrophylla (mahogany) and Pinus caribaea (Caribbean pine) in Fiji and T. grandis in Papua New Guinea and Solomon Islands. Climate values in a 10 minute grid (approximately 18 km spacing) are used to identify locations with climatically suitable conditions for the species. The impacts of climate change on plantations of all three target species in Fiji are considered to be low in 2030 and 2050. However, impacts may become medium for S. macrophylla and P. caribaea in 2080 using an A2 'business as usual' scenario, as some areas begin to fall outside climatically suitable limits for these species. The likely impacts of climate change on T. grandis sites in PNG and Solomon Islands are also assessed as low, as the main plantation areas remain largely in climatically suitable areas until at least 2050 under the A2 scenario. The implications for vulnerability of these plantations are discussed, along with strengths and weaknesses of the method, and possible further analyses. Une méthode simple est appliquée pour fournir une évaluation préliminaire des impacts du changement climatique sur les domaines d'implantation d' espèces pour Tectona grandis (teck), Swietenia macrophylla (acajou) et Pinus caribaea (pin des Caraïbes) à Fidji et T. grandis en Papouasie- Nouvelle-Guinée et Salomon Îles. Valeurs climatiques dans une grille de 10 minutes (à environ 18 km de distance) sont utilisés pour identifier les endroits avec des conditions climatiques appropriées pour les espèces. Les impacts du changement climatique sur les plantations des trois espèces cibles à Fidji sont considérés comme faibles en 2030 et 2050. Toutefois, les impacts peuvent devenir moyen pour S. macrophylla et P. caribaea en 2080 en utilisant un 'business as usual' A2 scénario, comme certaines régions commencent à tomber en dehors climatiquement limites appropriées pour ces espèces. Les effets probables du changement climatique sur T. grandis sites PNG et les Îles Salomon sont également jugés faibles, comme les principales zones de plantation restent largement dans les zones climatiquement adaptées au moins jusqu'en 2050 selon le scénario A2. Les implications de la vulnérabilité de ces plantations sont discutés, avec les forces et les faiblesses de la méthode, et d'éventuelles nouvelles analyses.Un método simple se aplica para proporcionar una evaluación preliminar de los impactos del cambio climático en los dominios de la plantación de especies de Tectona grandis (teca), Swietenia macrophylla (caoba) y Pinus caribaea (pino caribe) en Fiji y T. grandis en Papua Nueva Guinea y Salomón Islas. Los valores climáticos en una rejilla 10 minutos (unos 18 km separación) se utilizan para identificar lugares con condiciones climáticamente adecuadas para la especie. Los impactos del cambio climático en las plantaciones de las tres especies objetivo en Fiji se considera que son bajos en 2030 y 2050. Sin embargo, los efectos pueden llegar a ser medio para S. macrophylla y P. caribaea en 2080 utilizando un 'business as usual' A2 escenario, ya que algunas zonas comienzan a caer fuera climáticamente límites adecuados para estas especies. Los probables impactos del cambio climático en T. grandis sitios en PNG y las Islas Salomón también se evalúan tan bajo, ya que las principales áreas de plantaciones siguen en gran medida en las áreas climáticamente adecuadas por lo menos hasta 2050 bajo el escenario A2. Se discuten las implicaciones para la vulnerabilidad de estas plantaciones, así como las fortalezas y debilidades del método y los posibles nuevos análisis.